Early repolarization in the inferior leads after accessory pathway ablation is highly correlated with atrial fibrillation in Wolff–Parkinson–White syndrome. Issue 3 (March 2020) - Chen, Mu; Wang, Qunshan; Sun, Jian; Zhang, Peng-Pai; Li, Wei; Mo, Bin-Feng; Li, Yi-Gang
Highlights: Both early repolarization (ER) and atrial fibrillation (AF) are highly prevalent in Wolff-Parkinson-White syndrome (WPW). Inferior-lead ER after ablation is associated with AF recurrence in WPW patients. Additional pulmonary vein isolation might be considered in WPW patients with AF and ER. Abstract: Background: Both atrial fibrillation (AF) and early repolarization (ER) are highly prevalent in patients with Wolff–Parkinson–White (WPW) syndrome. Methods: We retrospectively identified 123 WPW patients with manifest accessory pathway (mAP) and 105 patients with concealed accessory pathways (cAP) who underwent successful ablation of the APs. AF history prior to the ablation was investigated. The presence of ER was evaluated from the 12-lead electrocardiograms performed both before and immediately after the ablation. Patients were further followed up for AF occurrence after the AP ablation. Results: Compared with cAP patients, WPW patients presented with higher incidence of previous AF, as well as ER after the AP ablation. Compared with those without AF history, WPW patients with comorbid AF were more prone to presenting ER, especially in the inferior leads, after the mAP ablation. Regression analysis suggested that the post-ablation ER in the inferior leads was strongly associated with AF in WPW patients [OR = 5.85; 95% confidence interval (CI): 2.29–14.96], even after adjusting for age and left atrial diameter (OR = 5.14; 95% CI: 1.80–14.74). Moreover, post-ablation inferior-lead ER was predictive of AF recurrence after mAP ablation during the follow-up of 22.6 ± 11.1 months. In comparison, ER was correlated with neither AF history nor AF recurrence in patients undergoing cAP ablation. Conclusions: ER in the inferior leads after the mAP ablation is highly correlated with AF history and recurrence in WPW patients.